Occurrence of deoxynivalenol (vomitoxin) in processed cereals and pulses in Turkey - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2003)
The aim was to investigate the occurrence of deoxynivalenol (DON) in cereal and pulse products in Turkey. DON was detected using high-performance liquid chromatography (HPLC) with ultraviolet detection at 220 nm and positive results greater or equal to 0.60 ppm were confirmed by thin layer chromatography (TLC). An acetonitrile-water (21:4 v/v) extract of the sample was cleaned up on a column packed with alumina Celite-charcoal (0.35 + 0.25 + 0.40 g). The detection limits for DON were 3 ng/injection (0.10 ppm) and 50 ng/spot (0.60 ppm) for HPLC and TLC, respectively. Eighty-three commercially available cereal and pulse product samples collected from markets and street bazaars were analysed. The recovery rates for boiled, pounded wheat and rice spiked with added DON (1 ppm) were 80.9% (SD 8.37, n = 5) and 72.3% (3.85, n = 5), respectively. DON was detected in six (8.82%) of 68 cereal and in none of 15 pulse products. The maximum detected amount was 2.67 ppm in a corn flour sample.
Keywords: deoxynivalenol; cereals and pulses; HPLC; TLC; TRICHOTHECENE MYCOTOXINS; ESOPHAGEAL CANCER; FUSARIUM; GRAINS; FOODS; WHEAT; CORN; ZEARALENONE; TOXINS; AREAS